Safety and Efficacy of Endoscopic and Microscopic Techniques for Facial Nerve Decompression After Trauma: A Systematic Review and Meta-Analysis - Paleare, Luis F. F.; Ferreira, Marcio Y.; Hong, Anthony; Santos, Ana B.; Bocanegra-Becerra, Jhon E.; Ribeiro, Filipe V.; Palavani, Lucca B.; Pereira, Anna; Fukunaga, Christian K.; Scarramal, João P. L.; Tedrus, João G. R.; Ferreira, Christian; Martinez-Perez, Rafael (Journal of Neurological Surgery Part B: Skull Base, 2025)
Facial nerve palsy (FNP) is a result of facial and temporal trauma, often requiring surgery. Endoscopic or microscopic nerve decompression is one of the main surgical treatments. However, robust evidence on the safety and efficacy of these techniques remains scarce in the literature. This systematic review and meta-analysis aimed to synthesize current data on the outcomes of these surgical techniques for traumatic FNP (tFNP).Following PRISMA guidelines, we searched PubMed, Embase, Web of Science, and the Cochrane Library. Studies included patients who underwent endoscopic or microscopic surgical treatment for tFNP. Outcomes were classified by the House–Brackmann (HB) score: complications after surgery, normal facial function to recovery from mild dysfunction, moderate to moderately severe dysfunction, and severe dysfunction to total paralysis after surgery. Analyses were conducted separately, with subanalyses for the transmastoid (TM), middle cranial fossa (MCF), and combined TM + MCF routes in studies reporting.A total of 26 studies with 597 patients were included. The overall complication rate was 2% for endoscopic and 3% for microscopic. Endoscopic outcomes showed HB I–II 88, HB III–IV 6, and HB V–VI 3%. Microscopy revealed HB I–II 66, HB III–IV 29, and HB V–VI 2%. The complication rates for the TM approach were 0, MCF, and TM + MCF combined were 3 and 2%. Furthermore, the HB I–II score rates were 66 (TM), 70 (MCF), and 58% (TM + MCF).Both techniques are safe and effective; better efficacy was analyzed with the endoscopic. Further studies with standardized populations are needed.
Keywords: facial decompression; facial nerve palsy; facial trauma; endoscopy; microscopy